A Novel and a Previously Described Compound Heterozygous PKLR Gene Mutations Causing Pyruvate Kinase Deficiency in a Chinese Child. (1st June 2014) - Li, Huimin; Gu, Ping; Yao, Ru-en; Wang, Jian; Fu, Qihua; Wang, Jing
<x xml:space="preserve">Abstract</x> Background: Pyruvate kinase deficiency (PKD) is one of the most common enzymatic defects in humans and it is an autosomal recessive disorder causing chronic nonspherocytic hemolytic anemia. Methods: A two-year-old male baby with severe hemolytic anemia and low level of pyruvate kinase (PK) activity was enrolled in this study. All exons of PKLR gene and their flanking sequences were amplified from the patient's genomic DNA using PCR. Bioinformatics software was used to evaluate the functional impacts of the mutations found in this study. Results: It was here demonstrated that the boy harbored a previously described mutation (c. 941T>C) in exon 7 and a novel mutation (c. 1183 G>C) in exon 9 of PKLR gene. Both mutations led to significant structural alterations and decreased enzymatic activity of PK, as predicted by tool software. Conclusions: The compound heterozygous mutations in the PKLR gene were the cause of inherited PKD for this patient.